Pemanfaatan Limbah Kain Perca Menjadi Produk Yang Memiliki Nilai Jual Pada Ibu-Ibu PKK Kelurahan Mintaragen Kota Tegal - Aan Umaroh; Ari Mulyani; Ika Titi Hidayati; Intan Latifah Sari; Khoerunisa; Mahes Solekhudin; Muhammad Iqbal; Saeful Umam; Sekha Rakhmani; Agus Riyanto (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Patchwork is one of the fabrics from convection waste that produces clothing. Convection produces a lot of patchwork waste which has inorganic properties, that is, it is difficult to process because it cannot be decomposed and cannot be composted. Seeing this problem, it is necessary to take action to minimize environmental pollution due to rag waste by utilizing it into products that have sales value such as mask connectors, tote bags, key chains, coasters, brooches and so on. The aim of this activity is to equip PKK women in Mintaragen Village, Tegal City, with skills in processing patchwork waste into products that have sales value, with these skills it is hoped that they can provide benefits to the residents' economy and minimize environmental pollution. The method used in this activity is the observation method carried out at the convection and the partners who will be invited to collaborate in this program, the interview method carried out at the convection and Mintaragen sub-districts regarding the program to be implemented, the socialization and training method aimed at partners, namely mothers PKK, Mintaragen Village, Tegal City. Overall, this program succeeded in achieving its goal, namely empowering PKK women to develop skills in processing materials that were previously considered waste into products of marketable value. Of the total participants, around 85% succeeded in producing products that were worth selling after attending a series of training over 3 meetings. Participants demonstrated improved sewing skills, creativity in design, and thoroughness in completing products. The evaluation results showed a significant increase in participants' skills and knowledge regarding recycling and entrepreneurship.